EFEK KATALITIK ZINC-OXIDE (ZNO) TERHADAP KINETIKA REAKSI PEMBAKARAN MATERIAL SAMPAH PADAT: THE CATALYTIC EFFECT OF ZINC-OXIDE (ZNO) ON THE KINETICS OF COMBUSTION REACTIONS OF SOLID WASTE MATERIALS - Citrakara Upendra Sneha Bandhana Kusuma Himawan; Rahmad, Hadi; Laksana, Alfian Hudan (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
This study aims to determine the catalytic effect of ZnO on the kinetics of the decomposition reaction of burning solid waste. ZnO catalyst was chosen because it has high mobility and reactivity. samples were prepared and randomly selected consisting of 12 types of inorganic waste and 10 types of organic waste. The research instrument uses (DTA) Differential Thermal Analysis proximate testing. From this test the data in the form of a mass decrease graph will be analyzed descriptively. The description of the data is displayed through the TG-DTG curve and the calculation of the activation energy (Ea) using the fitting model. the DTG curve identifies three peaks indicating the decomposition stages of the three components have different characteristics. The decomposed components are 1. lignocellulosic organic and low stability organic components, 2. Volatile substances from plastic components, 3. hydrocarbon residues and ash reformation. The combustion temperature increases in samples with high catalyst concentrations, but the burnout temperature decreases in samples with high catalyst concentrations. The DTA curve shows the increased reactivity of samples with high catalyst concentrations. Oxidative reactions which are exothermic/external heating increase in samples with high catalyst concentrations. The catalytic effect on the addition of zinc-oxide (ZnO) catalyst concentration to the components showed a decrease in the hydrocarbon component and an increase in the short chain hydrocarbon component. Increasing the concentration of zinc-oxide (ZnO) catalyst in the sample increases the activation energy. However, overall the addition of catalyst concentration in the combustion of organic-inorganic solid waste samples was able to reduce the activation energy at the end of the combustion reaction